Pemberdayaan Perempuan, Perlindungan Anak Dan Keluarga Pencegahan Pernikahan Dini Di Desa Petungsewu Kecamatan Dau Kabupaten Malang: Pemberdayaan Perempuan, Perlindungan Anak Dan Keluarga Pencegahan Pernikahan Dini - Cahyani, Desy Dwi; Kostania, Gita (Politeknik Kesehatan Kemenkes malang, 2023)
Early marriage forces girls to mature before they are emotionally and physically mature, and it has a negative impact on health, education, economic and social development. Data collection in this activity provided pre test and post-test before and after the material was also given through a Focus Group Discussion, the number of respondents was 40 people and the instrument used was a questionnaire. Most of them, namely 20 (50 percent) of respondents aged 20 until 35 years, Increased knowledge about Early Marriage and its Problems from initially not good enough, Increased Knowledge of Cadres about Women's Empowerment, Child and Family Protection in Prevention of Early Marriage from less to good . Community Service Activities in Petungsewu Village, Dau Subdistrict, are very much supported by the community, especially in increasing knowledge about early marriage and the impacts caused by early marriage